Quality Assurance Audit System for Legal Improvement of Foreign Investment in Indonesia - M.H, Nofriza, S.H.,; M.H, Tarsisius Murwadji, S.H.,; MH, Helza Nova Lita, SH, (Journal of Ecohumanism, 2024)
Foreign investment in Indonesia has been present since 1967, starting at the onset of the New Order era. It was initially regulated by Act No. 1 of 1967 concerning Foreign Investment and later updated by Act No. 25 of 2007 concerning Investment. The fact is, foreign investment does not always run smoothly; many problems arise due to incomplete regulations or insufficient benefits for business actors, especially foreign investors. Legal issues caused by the shortcomings of these regulations will impact deviations in their implementation. For foreign investors or business actors with bad intentions, the regulations' shortcomings can be exploited for their interests. The research metode involves literature research conducted through a literature review. This study finds that legal quality audits in investment law are designed to measure legal quality both against regulations (normative audit) and the application of these regulations in practice (implementative legal audit) in the investment sector. Also, the development of concepts in Indonesian National Economic Law based on legal quality science related to the regulation of state revenue from foreign sources involves the development of several concepts in the field of investment law.